(untitled) (Práxis Educativa, 2021)
In this article, we relate the concept of unity in diversity, developed by Paulo Freire, to educational actions that promote both academic achievement and improvement in social coexistence in diversity. Initially, we present key concepts elaborated by the author in different publications and we emphasize its relevance. Subsequently, we highlight the concept of unity in diversity and how it underpins Successful Educational Actions (SEA) for Youth and Adult Education, based on the results of a qualitative case study, developed between 2014 and 2016. Finally, we highlight the way that the theory and the comprehension that Paulo Freire offers us remains alive and current, mainly by demonstrating the history that has been built by men and women in favor of humanization and democratic education. Keywords: Unity in diversity. Successful Educational Actions. Humanization.